Equivalent Modeling Method for Thermal Calculation of Transformer Windings Based on Minimum Thermal Resistance - Liu, Chengxiang; Li, Yan; Yu, Zhanyang; Zhang, Chunhui; Mao, Yedong; Li, Jingmeng; Xu, Ge (Electronics (Basel), 2025)
In the accurate calculation of the temperature rise and hot spots of transformer windings, considering the inter-turn insulation will lead to a sharp increase in the workload of detailed modeling and a large number of mesh refinements. To address this issue, this paper proposes a calculation method for the equivalent thermal conductivity based on the minimum thermal resistance principle. This method can accurately calculate the equivalent thermal conductivities in the axial and radial directions of the windings. By using the disk windings model under the equivalent thermal conductivity, a temperature field analysis is performed on the actual windings with inter-turn insulation. To validate the method, models considering inter-turn insulation and equivalent models are constructed, and detailed analyses are performed using the empirical formula method and the equivalent method based on the minimum thermal resistance principle, respectively. By comparing the simulation results of the equivalent model and the model considering inter-turn insulation, it is found that the equivalent method based on the minimum thermal resistance principle not only significantly reduces the number of mesh elements but also achieves significantly improved accuracy in the temperature field analysis of the turn-divided model compared to the empirical formula method. Moreover, the winding temperature rise and hot spot positions before and after the equivalence are nearly identical and closer to the experimental results, demonstrating the validity of this method.